Canine separation anxiety: how first referral practices can help. (2nd September 2021) - Heirs, Morag; Graham, Heather
Abstract : There are currently approximately 10.1 million pet dogs in the UK, equating to about 26% of the UK adult population owning a dog. Early research indicates that dogs have played an essential role in helping their owners to cope throughout the COVID-19 pandemic. This article explores the potential impact of lockdown on the canine experience and the risk of developing separation-related behavioural problems, as well as how first referral veterinary practices can support their clients through this.